2001
DOI: 10.1093/emboj/20.20.5615
|View full text |Cite
|
Sign up to set email alerts
|

Repacking of the transmembrane domains of P-glycoprotein during the transport ATPase cycle

Abstract: This paper is dedicated to the memory of our friend and colleague Andreas Schmidlin P-glycoprotein (P-gp) is an ABC (ATP-binding cassette) transporter, which hydrolyses ATP and extrudes cytotoxic drugs from mammalian cells. P-gp consists of two transmembrane domains (TMDs) that span the membrane multiple times, and two cytoplasmic nucleotide-binding domains (NBDs). We have determined projection structures of P-gp trapped at different steps of the transport cycle and correlated these structures with function. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
248
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(269 citation statements)
references
References 56 publications
(83 reference statements)
21
248
0
Order By: Relevance
“…Spectroscopic studies of LmrA lead to a similar conclusion [45]. The nature of these conformational changes remains to be elucidated, although there is clearly a substantial repacking of the TMDs throughout the depth of the membrane [5,14]. Experimental evidence suggests that threading of α-helices into and out of the lipid bilayer is unlikely [46].…”
Section: Mechanisms Of Transportmentioning
confidence: 85%
See 4 more Smart Citations
“…Spectroscopic studies of LmrA lead to a similar conclusion [45]. The nature of these conformational changes remains to be elucidated, although there is clearly a substantial repacking of the TMDs throughout the depth of the membrane [5,14]. Experimental evidence suggests that threading of α-helices into and out of the lipid bilayer is unlikely [46].…”
Section: Mechanisms Of Transportmentioning
confidence: 85%
“…Although it has long been predicted from primary sequence data that the TMDs each consist of multiple membrane-spanning α-helices, it was only with the first X-ray structure, for a bacterial lipid transporter MsbA, that this was formally confirmed [7]. Low-to-medium resolution structures of the mammalian multidrug resistance P-glycoprotein (P-gp; ABCB1), obtained by electron microscopy of single particles [13] and electron cryomicroscopy of 2-D crystals [5,14], showed that the TMDs form an enclosed aqueous chamber/pore in the membrane which, in the basal state, appears open at the extracellular face but closed intracellularly, with the two NBDs exposed as cytoplasmic lobes (Fig. 1).…”
Section: Structure Of Abc Transportersmentioning
confidence: 99%
See 3 more Smart Citations